Peningkatan Minat Belajar dan Keaktifan Peserta Didik Pada Pembelajaran IPS di Kelas VII D SMPN 1 Gempol Dengan Menggunakan Video Pembelajaran dan World Wall - Istikomah Dewi; Irfan, Irfan; Karolina Ndundu; Aida Kurniawati; Wiwik Setyowati (FKIP, Universitas Palangka Raya, 2024)
This study aims to increase learning interest and activeness of students in the process of learning social studies in class VII D SMPN 1 Gempol by using learning videos and world wall applications.This type of research is class action VII D SMPN 1 Gempol which amounted to 30 children.The method used in collecting data is by observation (observation) and tests. The data analysis technique used is simple descriptive quantitative. With the innovation in learning media can increase interest in learning and activeness of students in the process of learning social studies in class VII D SMPN 1 Gempol, seen from the implementation of actions on learning from initial observations obtained level of interest in learning and activeness of students in cycle I average is 46.05, with 46.666% completeness of 14 students, and unfinished there are 11 students or 53.333%. Experiencing an increase in cycle II with an average of 89.70%, the completeness of 27 students 90% and those who have not completed there are 3 students or 10%, thus there is an increase in the interest in learning and the liveliness of students increases. The learning interest and activeness of students in cycle II has met the success indicators because approximately 80% have reached the Minimum Completeness.